2011
DOI: 10.2134/jeq2010.0497
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Odorants from Pig Production in Sampling Bags for Olfactometry

Abstract: Odor from pig production facilities is typically measured with olfactometry, whereby odor samples are collected in sampling bags and assessed by human panelists within 30 h. In the present study, the storage stability of odorants in two types of sampling bags that are often used for olfactometry was investigated. The bags were made of Tedlar or Nalophan. In a field experiment, humid and dried air samples were collected from a pig production facility with growing-finishing pigs and analyzed with a gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…The limit of detection (LOD, calculated as three times the standard deviation on blank samples) of our PTR-MS system with respect to volatile organic sulfur compounds is typically in the range of 0.02–0.15 ppb [2527], which is lower than LOD of some alternative methods, e.g., GC-PFPD (pulsed flame photometric detector) (0.5–2.4 ppb, three times the standard deviation) [28] and GC-ASD (amperometric sulfur detector) (around 5 ppb) [29]. However, the LOD of the PTR-MS used in this study is higher than found for GC-ToF-MS (0.122 ppt, three times the standard deviation of the background noise) [30], and the method detection limit (MDL) is often expected to be much higher than the LOD [30].…”
Section: Methodsmentioning
confidence: 99%
“…The limit of detection (LOD, calculated as three times the standard deviation on blank samples) of our PTR-MS system with respect to volatile organic sulfur compounds is typically in the range of 0.02–0.15 ppb [2527], which is lower than LOD of some alternative methods, e.g., GC-PFPD (pulsed flame photometric detector) (0.5–2.4 ppb, three times the standard deviation) [28] and GC-ASD (amperometric sulfur detector) (around 5 ppb) [29]. However, the LOD of the PTR-MS used in this study is higher than found for GC-ToF-MS (0.122 ppt, three times the standard deviation of the background noise) [30], and the method detection limit (MDL) is often expected to be much higher than the LOD [30].…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that the concentration of several typical odorants from animal houses (reduced sulfur compounds, amines, carboxylic acids, phenols and indoles) decreases during the storage in one or more types of sampling bags, possibly due to sorption to the bag material and diffusion out of the bags [2–6]. For certain compounds, e.g., phenols, the 24 h recovery is <10% [3,4,6]. …”
Section: Introductionmentioning
confidence: 99%
“…The odorous gas is typically collected, employing the lung principal, in tetrafluoroethylene hexafluoropropylene (FEP), polyvinyl fluoride (PVF, Tedlar) or polyethylene terepthalate (PET, Nalophan) sampling bags (Trabue, Kerr, Bearson, & Ziemer, 2011;Zhang et al, 2010). Odorous compounds may adsorb on the sampling bag surface or diffuse through the bag during storage or transport (Hansen, Adamsen, Feilberg, & Jonassen, 2011). This results in a sample that might be different in chemical composition when compared to the sample from which the odour had to be evaluated (van Harreveld, 2003).…”
Section: Bpmentioning
confidence: 99%